Potensi Jenis Tumbuhan Bawah Berkhasiat Obat di Hutan Kota Raggawulung, Kabupaten Subang - Dina Anggraini; Lily Surayya Eka Putri; Dasumiati Dasumiati (Al-Kauniyah: Jurnal Biologi, 2013)
The objective of this research was to know the understory species diversity and to identified the potency of medicinal plants in Ranggawulung Urban Forest. The method of this research is vegetation analysis using circular plot (4 m in diameter), we used 30 plot in the site. We counted number of individuals and species richness. Importance Value Index, Simpson’s, and Shanon-Wiener Index was calculated to describe it’s diversity. The result showed Ranggawulung Urban Forest had high of understory diversity (Shanon-Wiener Index 3,36).  There was 56 understory species, and 19 of them was identified as medicinal plants. There are Ageratum conyzoides, Piper aduncum, Sida rhombifoli, Eupatorium odoratum, and Turnera ulmifolia. The utilization of this potency and the effort to conserve both ex-situ and insitu are also elaborated.